Arsenic and hydrated silica removal from groundwater by electrocoagulation using an up-flow reactor in a serpentine array. Issue 5 (October 2019) - Castañeda, Locksley F.; Coreño, Oscar; Nava, José L.
Highlights: Abatement of arsenic and hydrated silica from groundwater by electrocoagulation, EC. Serpentine reactor, with aluminum electrodes, opened at the top to favor H2 release. Important aluminum doses are produced at current densities higher than 6 mA cm −2 . Silica reacts with aluminum to yield aluminosilicates as flocs. WHO and Mexican guidelines for As and hydrated silica were fulfilled after EC. Abstract: This paper concerns with the elimination of arsenic and hydrated silica from deep well water, collected form the septentrional area of Guanajuato in Mexico (arsenic 23 μg L −1, hydrated silica 154 mg L −1, sulphate 160 mg L −1, phosphate 0.3 mg L −1, pH 7.5 and conductivity 550 μS  cm −1 ) by electrocoagulation (EC) using an up-flow electrochemical reactor, opened to the atmosphere, with a six-cell stack in a serpentine array. Aluminum plates were used as electrodes. The efficiencies of arsenic and hydrated silica removal at different current densities (4 ≤ j ≤ 7 mA cm -2 ) and mean linear flow rates (1.2 ≤ u ≤ 4.8 cm s −1 ) were examined. The best EC was obtained at 7 mA cm -2 and 1.2 cm s −1, which satisfies the WHO guideline for arsenic (< 10 μg L −1 ) and permits the abatement of hydrated silica, giving values of electrolytic energy consumption and overall cost of EC of 1.64 kW h m -3 and 0.387 USD m -3, respectively. SEM-EDS, FXRD, XRD and FTIR analyses on the flocs revealed that they are structured mainly by aluminosilicates due to the reaction between aluminum and silica. While arsenates, sulfates and phosphates are removed by adsorption on aluminum flocs.